Life quality level as a target of art-therapeutic influence in the complex treatment of patients with schizophrenia - Krishtal, Alexandr (ScienceRise: Medical Science, 2017)
Aim: to study the life quality dynamics of patients with schizophrenia under the influence of art-therapy in the system of therapy and rehabilitation. Materials and methods: At the research there was realized the complex clinical-psychopathological examination of 125patients of both sexes, 20–45years old (mean age 35,0±2,0 years) with the set diagnosis schizophrenia in the period of stabilization. The main group (participated in art-therapy) included 95 persons (54 women and 41 men). The control group consisted of 30 patients (16 women and 14 men), who received the standard regulated treatment at hospital. Results of research. At the research there was used the system of art-therapy in the complex therapy of patients with schizophrenia and its effectiveness was proved. On the background of the complex therapy including art-therapy, there was observed the fast reduction of the psychopathological symptomatology, normalization of the emotional condition, stabilization of patients’ behavior, improvement of cognitive indices, increase of patients’ psychophysical activity. It was established, that on the background of using art-therapy in the complex treatment of patients with schizophrenia, the life quality index increased by all scales in the main group by 42,4 %, compared with the control– 26,9 %. Conclusions. Under the influence of art-therapy in the complex treatment of schizophrenia there was observed the fast reduction of psychopathological symptomatology, increase of the duration and quality of remission. There was established the high effectiveness of art-therapy compared with the traditional complex treatment as to improving the life quality of patients with schizophrenia. Art-therapy, based on elaborated principles for patients with schizophrenia is characterized by the higher effectiveness, compared with traditionally used methods